Quantification of pharmacokinetic profiles of a recombinant canine PD-1 fusion protein by validated sandwich ELISA method - Qiu, Jicheng; Yang, Yuxin; Kong, Jingyuan; Cao, Yuying; Liu, Yu; Luo, Haoshu; Cao, Xingyuan (Frontiers in Veterinary Science, 2022)
Tumors are becoming a serious threat to the quality of life of human and dogs. Studies have shown that tumors have caused more than half of the deaths in older dogs. Similar to human, dogs will develop various and highly heterogeneous tumors, but there are currently no viable therapies for them. In human, immunotherapy has been used widely and considered as an effective treatment for tumors by immune checkpoint targets, which are also expressed on canine tumors, suggesting that immunotherapy may be a potential treatment for canine tumors. In this work, we developed a sandwich ELISA method to detect the concentration of recombinant canine PD-1 fusion protein in canine serum and investigated pharmacokinetics in canines after intravenous infusion administration. After being validated, the ELISA method showed an excellent linear relationship in 25.00–3,200.00 ng/ml in serum, and the R2 was more than 0.99 with four-parameter fitting. The precision and accuracy of intra-assay and inter-assay at the five different concentrations met the requirements of quantitative analysis. At the same time, no hook effect was observed at the concentration above ULOQ, and the stability was good under different predicted conditions with accuracy > 80%. The pharmacokinetic study in dogs has shown that the recombinant canine PD-1 fusion protein exhibited a typical biphasic PK profile after intravenous infusion administration, and the linear pharmacokinetic properties were observed between 1.00 and 12.00 mg/kg. Meanwhile, the T1/2 after intravenous infusion administration with non-compartmental analysis was about 5.79 days.